Pengetahuan Petani Jagung Tentang Perubahan Iklim di Desa Rasau Jaya 1 Kabupaten Kubu Raya - Yunarni, Latifah; Yurisinthae, Erlinda; Suharyani, Anita (Hasanuddin University, 2025)
Climate change has become a serious challenge that must be addressed by the agricultural sector in Indonesia. One of the agricultural commodities that is particularly vulnerable to climate change is food crops such as maize. Maize is a strategic crop and plays an important role in food security, especially as a source of food for humans and feed for livestock. The purpose of this study is to determine the level of knowledge of maize farmers regarding climate change and to identify the factors that influence their level of knowledge. This research employs a nominal scale and logit analysis using the accidental sampling method. The study was conducted in Rasau Jaya 1 Village, Kubu Raya Regency. The method used in this study is descriptive quantitative by analyzing the farmers who are aware and unaware of climate change, as well as the factors that influence their knowledge. The population in this study comprises all maize farmers in Rasau Jaya 1 Village, totaling 629 farmers. The respondents consisted of 42 maize farmers, selected using the Slovin formula. The results of the study show that the majority of farmers are aware of climate change, and the factors that influence farmers' knowledge are age, farming experience, and access to information. Based on these findings, it is recommended that the government or the agriculture office enhance extension services and provide farmers with the necessary access to information. Additionally, the village government is encouraged to facilitate hamlet-based training programs to reach a broader number of farmers.